If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2h + 1 + -2h = 0 Reorder the terms: 1 + 2h + -2h = 0 Combine like terms: 2h + -2h = 0 1 + 0 = 0 1 = 0 Solving 1 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2(x-a)=y | | 4(3d-5)=4 | | x(7-3x)(6+x)=0 | | -3(x-8)+9=33 | | x^2-5x-204=0 | | C=0.5x | | x^2-5x+204=0 | | 40-3x=13 | | x^2+5x+204=0 | | 6(2p-1)2-54=0 | | -3=-n | | 4g+3(-6+3g)=1-g | | p-42=-42 | | -7x-2=-5x+6 | | (x^2+25)(x^2-9)=0 | | -4(-C-16)=-4-16 | | 0=t*lnt | | C=0.5x+22.4 | | 9y-5=23+2y | | 8(x+3)=38 | | 0.5x+9=-4 | | 9p-19=-61+2p | | x^2=-3x+9x | | 2(x-7)+3-5x=23 | | -3+p/6=-5 | | -6.9x+23.3831=-1.1(x-4.237) | | (-2+-2y)+3y=-4 | | 4+11x=7x-1 | | 7x+23x-5=6(5x+8) | | 10x-9=-11 | | 936-(x+24)=72 | | 4x-4+2y=0 |